AN IMPROVED SURVEILLANCE SYSTEM ARCHITECTURE BASED ON FLAME DETECTION IN CCTVS - ChangYong Ri; JinHyok Ju; HakSong Ri; KyongChol Rim (ICTACT Journal on Image and Video Processing, 2018)
CCTV is an important part of the surveillance systems. While a person observes the screens with the naked eye in existing CCTV monitoring systems, it is possible that the flame and events are not detected opportunely due to eye fatigue and human carelessness. In this paper, we propose a real-time flame detection method and design architecture of surveillance system to achieve early fire detection. When flame is detected, this system displays the video sequence from the corresponding camera channel on the whole screen with the alarm signal.